Comparative Effectiveness of Video and Picture Media on Students’ Biology Learning Outcomes - Janah, Nur; Mahrus, Mahrus; Khairuddin, Khairuddin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Learning media play a crucial and inseparable role in the teaching and learning process. Appropriate learning methods and media, such as videos and images, are necessary to facilitate students' understanding of the material presented by the teacher, ultimately maximizing learning outcomes. This study aims to determine the differences in biology learning outcomes using video media and images in Class VII of SMPN 1 Gunungsari. This type of research is a quasi-experimental study. The population of this study consisted of all students in class VII, comprising 10 classes with a total of 340 students. This study employed two classes: the experimental class and the control class. This study employed a purposive sampling technique, where the sample consisted of students who were more active and had stable learning outcomes. The experimental class consisted of 33 students, and the control class consisted of 33 students, resulting in a total sample of 66 students. The experimental class received learning through video media, while the control class used images. The results of this study showed that the average post-test score of the experimental class was 92.09, and the average post-test score of the control class was 80.06. Thus, the learning outcomes of students taught with video media were better than images. The results of the independent sample t-test showed a significant (2-tailed) value of 0.000 (p < 0.05), indicating a difference in biology learning outcomes between video media and images in class VII students of SMPN 1 Gunungsari.